Ambiguity Degrees of Courtesy in Trial: Ethical and Legal Norms, Legal Reasoning in Judicial Decisions - Helmi, Muhammad Ishar; Pujiyono, Pujiyono; Zada, Khamami; Encep, Encep (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Courtesy reasons are the basis for the legal reasoning of mitigation, as stated in the decision. Courtesy reasons only happen in one case. The Criminal Code explains the aggravating and mitigating circumstances of a sentence that is not considered decent in a conference. Explicitly, the word courtesy is not a reason to lighten the sentence. Article 197, paragraph 1, letter f of the Criminal Procedure Code contains the words "articles of statutory regulations which are the basis for punishment or action and articles of statutory regulations which are the legal basis of the decision." This paper uses normative legal research methods to analyze legal problems with analytical and prescriptive discipline. The findings in this research show that courtesy is not worthy of consideration in the decision as a basis for mitigation. Courtesy is an obligation for all parties in a court conference. Because when a party does not act politely, it is a crime against the judiciary or an insult to the Court. Also, courtesy norms are individual subjectivities that cannot be determined by law, especially by judges. Judges do not judge ethical norms but legal norms. The legal norms align with criminal law in that the use of norms of courtesy causes their application to criminal law because of their abstract and different nature.